1978
DOI: 10.1084/jem.147.3.897
|View full text |Cite
|
Sign up to set email alerts
|

The lymphoreticular system in triggering virus plus self-specific cytotoxic T cells: evidence for T help.

Abstract: The thymus determines the spectrum of the receptor specificities of differentiating T cells for self-H-2; however, the phenotypic expression of T cell's specificity for self plus virus is determined predominantly by the H-2 type of the antigen presenting cells of the peripheral lymphoreticular system. Furthermore, virus specific helper T cells are essential for the generation of virus-specific cytotoxic T cells. For cooperation between mature T cells and other lymphocytes to be functional in chimeras, thymic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
116
3

Year Published

1978
1978
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(129 citation statements)
references
References 34 publications
(48 reference statements)
10
116
3
Order By: Relevance
“…This does not mean that help would be required in CTL responses to all other antigens as well. We found that in completely allogeneic chimeras excellent CTL responses to H-2 antigens were obtained which, according to the suggestion of Zinkernagel et al (8), would be independent of T-cell help. …”
Section: Involvement Of Helper Cells In Thementioning
confidence: 64%
“…This does not mean that help would be required in CTL responses to all other antigens as well. We found that in completely allogeneic chimeras excellent CTL responses to H-2 antigens were obtained which, according to the suggestion of Zinkernagel et al (8), would be independent of T-cell help. …”
Section: Involvement Of Helper Cells In Thementioning
confidence: 64%
“…Nonetheless, on the basis of mostly indirect results from a variety of experimental approaches, the most prevalent model of CTL activation is one that closely parallels models of B cell activation, i.e., that I regionrestricted helper T cells activated by interaction with antigen in the context of I region determinants deliver inducing signals to antigen-activated precursor CTL (1)(2)(3)(4)(5). In some models, the helper T cell interacts with CTL precursors via the restricted recognition of I region determinants expressed by the CTL precursor (1,2).…”
mentioning
confidence: 99%
“…Nonetheless, on the basis of mostly indirect results from a variety of experimental approaches, the most prevalent model of CTL activation is one that closely parallels models of B cell activation, i.e., that I regionrestricted helper T cells activated by interaction with antigen in the context of I region determinants deliver inducing signals to antigen-activated precursor CTL (1)(2)(3)(4)(5). In some models, the helper T cell interacts with CTL precursors via the restricted recognition of I region determinants expressed by the CTL precursor (1,2). Experiments interpreted as supporting the role of I region-recognition events during the process of CTL induction include (a) studies demonstrating the augmentation of CTL responses to foreign H-2K and D antigens by I region-reactive T cells (5,6), (b) studies of CTL responses to viral (2) or non-H-2 cell surface antigens (7) or hapten (8), demonstrating an influence of I region genes expressed by cells of the thymus on the response phenotype of T cells that mature therein, (c) a study demonstrating the apparent depletion, by in vivo negative selection procedures, of I region-restricted helper cells required for an in vitro secondary CTL response specific for minor histocompatibility antigens (9), and (d) the finding that Ia + non-T accessory cells are required for in vitro CTL responses (4, 10, 1 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A gene regulating testosterone metabolism is linked to the major histocompatibility complex (H-2) of the mouse (72). Finally, during differentiation of T cells, the ability to recognize "self" versus "'nonself" with respect to the ability to respond normally to virus infections is determined by the thymic epithelial cells and not other cells of the body (73). These epithelial cells are the source of the thymic hormones.…”
Section: Endocrine Status With Respect To Age and Immunitymentioning
confidence: 99%